2014
DOI: 10.1590/sajs.2014/20140018
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise richness as an important characteristic of South African towns

Abstract: Towards the end of the 20th century there were almost 500 small towns of fewer than 50 000 persons in South Africa, accommodating about one tenth of the country's population. Little was known or said in national debates about the future of these places. A decade later this situation had changed and many studies have been or are being undertaken on small towns. For instance, the South African Government recognised that to stem the continued migration from rural to urban areas, a different approach was needed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Given the statistically significant relationships between population sizes and enterprise numbers frequently recorded for South African towns, [7][8][9][10][11][12][13][14][15][16][17][18][19] it is clear that town size (measured by the population number), the creation of jobs, and thus enterprise numbers and entrepreneurial decisions, have similar variance patterns. It is, therefore, also necessary to examine if the enterprise numbers of regions have Pareto rank-size distributions.…”
Section: Population and Enterprise Distribution In Citiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the statistically significant relationships between population sizes and enterprise numbers frequently recorded for South African towns, [7][8][9][10][11][12][13][14][15][16][17][18][19] it is clear that town size (measured by the population number), the creation of jobs, and thus enterprise numbers and entrepreneurial decisions, have similar variance patterns. It is, therefore, also necessary to examine if the enterprise numbers of regions have Pareto rank-size distributions.…”
Section: Population and Enterprise Distribution In Citiesmentioning
confidence: 99%
“…This result is not unexpected given the often-observed linear relationship between population sizes and enterprise numbers of South African towns. [7][8][9][10][11][12][13][14][15][16][17][18][19] If the rank-size population distribution of towns in a region is described by a power law, the enterprise number rank-size distribution of the region should exhibit the same pattern. The ratios observed for the enterprise distribution of the three regions indicate that lower-ranked towns in the three regions have from 50% to over 60% of the enterprises of the towns ranked just above them (Table 5).…”
Section: Enterprise Number Rank-size Distributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…These questions led to a study of a group of 134 South African towns. 4 It was found that the abundance of enterprise types is a function of the total enterprise numbers of the towns and follows a power law with an exponent of 0.7164. (Ball 5 remarked that there is no hidden Hobbesian significance in the word 'power' -it is just a mathematical term.…”
Section: Introductionmentioning
confidence: 99%